Civil society in Southeast Asia - LEE, Hock Guan (Institute Southeast Asian Studies, 2004)
What is the relevance of civil society to people empowerment, effective governance, and deepening democracy? This book addresses this question by examining the activities and public participation of non-governmental organizations (NGOs) in the areas of religion, ethnicity, gender and the environment. Examples are taken from Indonesia, Malaysia, the Philippines, Singapore, Thailand and Vietnam. State regimes' attempts to co-opt the concept or reject it as alien to "Asian values" have apparently not turned out as expected. This is evident from the fact that many Southeast Asian citizens are inspired by the civil society concept and now engage in public discourse and participation. The experience of civil society in Southeast Asia shows that its impact -- or lack of impact -- on democratization and democracy depends on a variety of factors not only within civil society itself, but also within the state.